Carbon Pricing Watch 2015 - Kossoy, Alexandre; Peszko, Grzegorz; Oppermann, Klaus; Prytz, Nicolai; Gilbert, Alyssa; Klein, Noemie; Lam, Long; Wong, Lindee (World Bank, Washington, DC, 2015)
Significant progress in carbon pricing has been made over the last ten years. In 2015, about 40 national and over 20 subnational jurisdictions, representing almost a quarter of global greenhouse gas emissions (GHG), are putting a price on carbon. Together, the carbon pricing instruments in these jurisdictions cover about half of their emissions, which translates into approximately 7 GtCO2e or about 12 percent of annual global GHG emissions. This figure represents a threefold increase over the past decade. The total value of the emissions trading schemes (ETSs) reported in the State and Trends of Carbon Pricing 2014 report was about US$30 billion (US$32 billion to be precise). Despite the repeal of Australia’s Carbon Pricing Mechanism in July 2014, and mainly due to the launch of the Korean ETS and the expansion of GHG emissions coverage in the California and Quebec ETSs, the value of global ETSs as of April 1, 2015 increased slightly to about US$34 billion. In addition, carbon taxes around the world, valued for the first time in this report, are about US$14 billion. Combined, the value of the carbon pricing mechanism globally in 2015 is estimated to be just under US$50 billion.